REDEFINING CITIZENSHIP IN DEMOCRATIC STATES: TOWARD A PUBLIC-CENTERED GOVERNANCE PARADIGM IN INDONESIA - Wicaksono, Kristian Widya; Komang Monday Sari (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2026)
This article advances a comprehensive reconceptualization of citizenship as a linchpin of democratic governance in contemporary Indonesia. Moving beyond the conventional legalistic paradigm, it posits citizenship as a multidimensional construct encompassing fiscal responsibility, electoral accountability, digital engagement, and social justice advocacy. Drawing on interdisciplinary frameworks—including social contract theory, lived citizenship, and collaborative governance—the study argues that democratic resilience in plural societies necessitates institutional reforms, inclusive political culture, and active civic agency. Empirical insights from Indonesian policy practices and comparative scholarship demonstrate that elite domination, bureaucratic inertia, and technocratic governance undermine democratic legitimacy. The article proposes a public-centered governance model anchored in participatory mechanisms, transparency, and civic co-production. It concludes that institutionalizing such practices is imperative for sustaining Indonesia’s democratic trajectory amid socio-political complexity and fiscal constraints.